Effects of Pilates-Based Exercise on Diastasis Recti Abdominis, Pelvic Floor Function, and Musculoskeletal Pain Across the Perinatal Period: A Narrative Review - Chmielowiec, Julia Marzanna; Czyżewicz, Zuzanna; Dworak, Kinga; Trędota, Natalia; Posid, Dominika; Lewczuk, Michał; Dańda, Karol; Chludek, Aleksandra; Chobot, Barbara; Wachowska, Marta (Quality in Sport, 2026)
Pregnancy and childbirth induce physiological changes affecting posture, abdominal wall integrity, and pelvic floor function. Diastasis recti abdominis affects up to 60% of women during pregnancy, pelvic floor dysfunction occurs in approximately 40% postpartum, and lumbopelvic pain persists in about 25% of women beyond early recovery. Pilates-based exercise offers an integrated approach combining breathing control, core activation, and pelvic floor training, potentially addressing multiple aspects of perinatal recovery simultaneously. Despite increasing clinical interest, evidence regarding its effectiveness across pregnancy and the postpartum period remains inconsistent. The aim of this narrative review is to synthesize current evidence on the effects of Pilates-based exercise on diastasis recti abdominis, pelvic floor function, and musculoskeletal pain in prenatal and postpartum women, with focus on program characteristics, intervention timing, and evidence quality. A literature review was conducted using PubMed, Scopus, Web of Science, PEDro, CINAHL, and the Cochrane Library. Studies published mainly between 2019 and 2024 were included, emphasizing randomized controlled trials, systematic reviews, and meta-analyses. Search terms included “Pilates,” “pregnancy,” “postpartum,” “diastasis recti,” “pelvic floor,” and “lumbopelvic pain.” Current evidence suggests that Pilates-based exercise may support perinatal musculoskeletal rehabilitation, including reduced labor pain, decreased inter-recti distance postpartum, and pelvic floor outcomes comparable to conventional training. However, limitations include small sample sizes, heterogeneous protocols, and inconsistent findings. Pilates may be considered a safe, potentially effective intervention when appropriately modified and integrated into individualized care plans.